Nonlinear Dynamic Analysis of Seismically Base-Isolated Structures by a Novel OpenSees Hysteretic Material Model - Nicoló Vaiana; Raffaele Capuano; Salvatore Sessa; Francesco Marmo; Luciano Rosati (Applied Sciences, 2021)
The complex response characterizing elastomeric isolation bearings is reproduced by employing a novel uniaxial hysteretic model that has been recently formulated and successfully implemented in OpenSees. Such a novel OpenSees material model offers several advantages with respect to differential models typically available in commercial software products for structural analysis, such as 3D-BASIS and CSi programs. Firstly, it is based on a set of only five model parameters that have a clear mechanical significance; such a property not only allows one to drastically simplify the parameters identification process, but it also allows the model to be used in practice. In addition, the model does not require numerical methods for the evaluation of the restoring force since the latter is computed by solving an algebraic equation. To encourage researchers and designers to adopt the proposed model for research and practical purposes, we demonstrate its accuracy by performing some numerical tests in OpenSees. In particular, we first employ the recently implemented model to compute the nonlinear dynamic response of a seismically base-isolated structure with elastomeric bearings and, subsequently, we compare the results with those obtained by modeling the seismic isolators with the OpenSees BoucWen uniaxial material model, that is one of the most popular and accurate hysteretic models currently available in OpenSees.